2013
DOI: 10.1016/j.ijid.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of antibodies for 42 months following vaccination of adolescents with a meningococcal serogroups A, C, W-135, and Y tetanus toxoid conjugate vaccine (MenACWY-TT)

Abstract: These results indicate that seroprotection following primary vaccination with MenACWY-TT extends more than 3 years. Ongoing persistence data are required to understand the duration of protection following vaccination and to guide decisions on the need for future booster doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
4
14
0
Order By: Relevance
“…The rapid decline in hSBA titers following a single dose has been observed with other group A meningococcal conjugate vaccines (16)(17)(18)(19)(20) and is consistent with observations reported in this population for rSBA GMT and IgG GMC. However, the magnitude of hSBA response is much less, and by threshold analyses, hSBA persists in a smaller proportion of the immunized group than indicated by rSBA or IgG ELISA immunoassays (2).…”
Section: Discussionsupporting
confidence: 90%
“…The rapid decline in hSBA titers following a single dose has been observed with other group A meningococcal conjugate vaccines (16)(17)(18)(19)(20) and is consistent with observations reported in this population for rSBA GMT and IgG GMC. However, the magnitude of hSBA response is much less, and by threshold analyses, hSBA persists in a smaller proportion of the immunized group than indicated by rSBA or IgG ELISA immunoassays (2).…”
Section: Discussionsupporting
confidence: 90%
“…[36][37][38] Although the hSBA assay is the most commonly used serologic marker of protection, this assay is difficult to standardize due to the nature of the reagents used. [39][40][41] The bactericidal assay using complement derived from baby rabbit serum (rSBA) is a widely accepted alternative to the hSBA. The rSBA assay generally yields higher titers than are seen in the hSBA.…”
Section: Rapid Waning Of Serogroup a Responses After Single Or Multipmentioning
confidence: 99%
“…55 In another smaller study including 36 adolescents 15 to 19 years old, a single dose of MenACWY-TT vaccine was compared to Men-PS at 42 months following vaccination. 61 All subjects in each group had serum bactericidal activity titers 1:8 against all serogroups at 42 months post-vaccination with higher GMTs than pre-vaccination titers, except for two subjects in the Men-PS group against serogroup C.…”
Section: Antibody Persistence Studiesmentioning
confidence: 84%
“…59 In addition, in the 42-month persistence study by Ostergaard et al, no SAEs among the 50 vaccinated adolescents were reported during this period. 61 In another randomized trial by Dbaibo et al, conducted at a center in Lebanon and three centers in the Philippines, MenACWY-TT had an adequate safety profile with pain (19.4%) and headache (16.3%) being the most commonly reported AEs in recruited adults 18 to 55 years old. 58 Grade 3 AEs were rarely reported in the MenACWY-TT and Men-PS groups.…”
Section: Adolescents and Adultsmentioning
confidence: 94%